Leveraging Social Media Platforms for Communicative Competence Development in English as a Foreign Language - Fitriani, Rani Siti; Rajkumar, S.R.; Nabila, Riva; Arif, Muhamad; Rafli, Muhammad (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The integration of social media stages into English as a Foreign Language (EFL) instruction has developed as a energetic approach to improving learnersâ communicative competence in bona fide and intuitively computerized situations. This think about investigates the educational potential of social media apparatuses such as Facebook, WhatsApp, Instagram, and YouTube in supporting the improvement of phonetic, sociolinguistic, and key competencies among EFL learners. Drawing upon later observational thinks about and hypothetical systems, the investigate investigations how social media encourages real-time communication, collaborative learning, and introduction to different social and etymological inputs. Discoveries demonstrate that when deliberately coordinates, social media improves learnersâ inspiration, dialect hone openings, and certainty in utilizing English for significant interaction past the classroom. Be that as it may, challenges such as advanced diversion, dialect exactness concerns, and educator readiness were moreover recognized. The ponder concludes by proposing academic procedures for compelling social media integration to boost communicative competence improvement whereas tending to potential confinements. These experiences contribute to planning inventive, learner-centred EFL educational module adjusted with modern advanced proficiency and communicative instructing standards.